1H‐NMR Fingerprinting of Vaccinium vitis‐idaea Flavonol Glycosides. Issue 5 (23rd May 2013) - Riihinen, Kaisu R.; Mihaleva, Velitchka V.; Gödecke, Tanja; Soininen, Pasi; Laatikainen, Reino; Vervoort, Jacques M.; Lankin, David C.; Pauli, Guido F.; de, Victor; Comte, Gilles; Santos‐Buelga, Celestino
ABSTRACT Introduction The fruits of Vaccinium vitis‐idaea L. are a valuable source of biologically active flavonoid derivatives. For studies focused on the purification of its quercetin glycosides (QGs) and related glycosides from plants and for the purpose of biological studies, the availability of numeric datasets from computer‐assisted 1H iterative full spin analysis (HiFSA), that is, 1H‐NMR fingerprinting, can replace and assist the repetitive and tedious two‐dimensional NMR identification protocol required for both known and new compounds, respectively. Objective To fully interpret the complex 1H‐NMR fingerprints of eight QGs obtained from the berries of V. vitis‐idaea and provide complete and unambiguous signal assignments. Methods Vaccinium vitis‐idaea QGs were purified in a single run by long‐bed gel permeation chromatography and identified by comparison with commercially available compounds using LC–MS combining ion‐trap and time‐of‐flight detection and one‐ or two‐dimensional NMR. The HiFSA analysis yielded full sets of 1H chemical shifts and proton–proton coupling constants, allowing for field‐independent spectral simulation. Results Signal assignments were achieved for the reference standards and the QGs that dominated in purified fractions. However, even mixtures of two to three QGs could be fitted using the HiFSA approach. In the case of the overlapped sugar resonances, the initial fitting of the 1H spectra of reference compounds, together with values extracted from the two‐dimensional NMR data and literature data, assisted in the process. Conclusion The HiFSA method revealed for the first time the presence of Q‐3‐O‐β‐glucopyranoside and Q‐3‐O‐β‐glucuronopyranoside in the berries of V. vitis‐idaea, and unambiguously confirmed the structures of Q‐3‐O‐[4″‐(3‐hydroxy‐3‐methylglutaroyl)]‐α‐rhamnopyranoside, Q‐3‐O‐α‐rhamnopyranoside, Q‐3‐O‐β‐galactopyranoside, Q‐3‐O‐α‐arabinofuranoside, Q‐3‐O‐β‐xylopyranoside and Q‐3‐O‐α‐arabinopyranoside. Copyright © 2013 John Wiley & Sons, Ltd.